Benefits and threats of free trade - Drozdz, Jolanta; Miškinis, Algirdas (Wolny handel. Koszty i korzyści, 2011)
The aim of the paper is to prepare common approach to trade liberalization with reference to theoretical review on the main benefits and threats of free trade. Several objec-tives are discussed: trade liberalisation concept, feasible benefits and advantages of free trade, potential threats and disadvantages of free trade, common approach to trade liberalization at country’s, organisation’s, and consumer’s levels. Judging from recent economic crises, free and open markets will be a necessary precondition for a sustained economic recovery; therefore, addressing policies with both direct and indirect impacts on trade will be of an immense importance. The main task is to liberalise trade reasonably and avoid as many drawbacks as possible
Ekonomia = Economics, 2011, Nr 2 (14), s. 40-48
Keywords: free trade; liberalization; benefits of free trade; threats of free trade